Pengelolaan Pembelajaran Biologi di SMP Negeri 1 Boyolali - Arimpi, Anis (Jurnal Varidika: Varia Pendidikan, 2013)
The reseachâs purposes are (1) to describe the characteristics of biology learning plan at SMP Negeri 1 Boyolali, (2) to describe the characteristics of biology learning process at SMP negeri 1 Boyolali, (3) to describe the characteristics of evaluation of biology learning process at SMP Negeri 1 Boyolali. This is a descriptive qualitative research which is carried out at SMPN 1 Boyolali. The subjects of the reseacrh are the principal, biology teacher and student of SMPN 1 Boyolali. Data collection technique used in this research are observation, interview and documentation. Data analysis technique used are data collection, data reduction, data presentation and conclusion.In this reseach, the validity of the data consists of credibility, reliability, and objectivity.The result of this research are (1) the characteristic of biology learning plan at SMP Negeri 1 Boyolali is started by arranging syllabus, followed by arranging annual plan, semester plan, and lesson plan.(2) the characteristic of biology learning process at SMP negeri 1 Boyolali is started by doing aperception, and carried out with some learning methods which are able to increase the learning achievement. The methods use are tutorial, discusion, demonstration, CTL and task giving teaching aids used in the biology lesson are LCD, computer, worksheet which of course, match the teaching material given (3) characteristic evaluation at SMP 1 Boyolali carried out in the form of daily test, mid semester test, semester test, and practice result of the student.